Proteolytic cleavage and truncation of NDRG1 in human prostate cancer cells, but not normal prostate epithelial cells. Issue 3 (11th June 2013) - Ghalayini, Mohammad K.; Dong, Qihan; Richardson, Des R.; Assinder, Stephen J.
Abstract : NDRG1 ( N -myc downstream regulated gene-1) is a metastasis suppressor that is down-regulated in prostate cancer. NDRG1 phosphorylation is associated with inhibition of metastasis and Western blots indicate two bands at ~41 and ~46 kDa. Previous investigations by others suggest the higher band is due to NDRG1 phosphorylation. However, the current study using a dephosphorylation assay and the Phos-tag (phosphate-binding tag) SDS/PAGE assay, demonstrated that the 46 kDa NDRG1 protein band was not due to phosphorylation. Further experiments showed that the NDRG1 protein bands were not affected upon glycosidase treatment, despite marked effects of these enzymes on the glycosylated protein, fetuin. Analysis using RT–PCR (reverse transcriptase–PCR) demonstrated only a single amplicon, and thus, the two bands could not result from an alternatively spliced NDRG1 transcript. Western-blot analysis of prostate cancer cell lysates identified the 41 kDa band to be a truncated form of NDRG1, with MS confirming the full and truncated proteins to be NDRG1. Significantly, this truncated protein was not present in normal human PrECs (prostate epithelial cells). Western-blot analysis using anti-NDRG1 raised to its N-terminal sequence failed to detect the truncated protein, suggesting that it lacked N-terminus amino acids (residues 1–49). Sequence analysis predicted a pseudotrypsin protease cleavage site between Cys 49 –Gly 50 . Such cleavage of NDRG1 in cancer cells may result in loss of NDRG1 tumour suppressive activity.